النظام الجبائي الجزائري- قراءة في البنية والهيكل على ضوء المستجدات الأخيرة - Harrag, Masbah (Finance and Business Economies Review, 2018)
The fiscal and customs system play a significant role in making the state’s economical orientations consider very much the strategic importance of fiscal and customs policies and their impact when the biggest aims of the state are planned. Hence, this importance has been sustained by overcoming the traditional notion of fiscality that considers if not more than a source of tax collection and a means of obtaining financial resources for funding the public spending, to a more complex role that involves economical orientations and the redressing of the derivations of the economical policies. Also, the efficiency of the fiscal abundance does not simply mean a big outcome of tax collection, though, fiscality in its simplest notion should not be marginalised as an important financial source; it is a strict measurement and a summary of a group of economical and social norms. Hence, the fiscal policies should be planned according to some scientific criteria either in their theoretical concepts or the practical ones to be sure of their efficacy., and that was to obtain some objectives such as:  Financial objectives:To improve the level of financing by replacing oil tax with normal tax.  Technical objectives: By adding notions such as: simplicity, flexibility and efficiency to the Algerian fiscal system.  Constructional objectives: By modernising and updating the fiscal management administration